2000
DOI: 10.1007/s11663-000-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

Rate of slag reduction in a laboratory electric furnace—alternating vs direct current

Abstract: The objective of this laboratory investigation was to measure the reduction kinetics of nickel smelting and converting slags using alternating current (AC) and direct current (DC). The two slags tested contained 34 and 51 pct total iron in the form of FeO and Fe 3 O 4 . Laboratory experiments were carried out between 1200 ЊC and 1450 ЊC, and the rate of reduction was measured based on the CO and CO 2 contents in the off-gas from the furnace. Upon application of power to a pair of electrodes immersed in the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The relevance of the se as the EoL battery availability expands in the near future. One e to use existing pyrometallurgical processes, such as the slag onsequently, to improve the environmental targets and decrease rocess on fossil fuels, utilizing biochar instead of coke would be a el smelting slags regarding cobalt, nickel and copper recoveries as vestigated very limitedly [25][26][27][28]. Studies determining the rate n oxides [29] and iron-silicate slags [30,31] exist and most of them n/the Boudouard reaction is the controlling step but also chemical diffusion and convection mechanisms, have been proposed [32,33].…”
Section: Slag Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of the se as the EoL battery availability expands in the near future. One e to use existing pyrometallurgical processes, such as the slag onsequently, to improve the environmental targets and decrease rocess on fossil fuels, utilizing biochar instead of coke would be a el smelting slags regarding cobalt, nickel and copper recoveries as vestigated very limitedly [25][26][27][28]. Studies determining the rate n oxides [29] and iron-silicate slags [30,31] exist and most of them n/the Boudouard reaction is the controlling step but also chemical diffusion and convection mechanisms, have been proposed [32,33].…”
Section: Slag Compositionmentioning
confidence: 99%
“…The reduction kinetics of nickel smelting slags regarding cobalt, nickel and copper recoveries as a function of time have been investigated very limitedly [25][26][27][28]. Studies determining the rate controlling steps of reduction of iron oxides [29] and iron-silicate slags [30,31] exist and most of them suggest that the carbon gasification/the Boudouard reaction is the controlling step but also chemical reaction and mass transfer, that is, diffusion and convection mechanisms, have been proposed [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of papers [11][12][13][14][15][16][17][18][19][20][21][22] devoted to the study on the kinetics of the reduction of FeO and Fe 2 O 3 oxides from slags, but only few deal with the reduction of noneferrous metals from slags. Therefore, an extensive study on the kinetics of copper recovery from industrial slags was undertaken to improve effectiveness of the copper recovery in Głogów smelter.…”
Section: +mentioning
confidence: 99%
“…El-Rassi and Utigard [20] have studied the reduction kinetics of the nickel smelting and converting slags under the conditions when alternating or direct current was passing through these slags. They observed that the reduction rate increases with the increasing electric power input and the slag temperature.…”
Section: +mentioning
confidence: 99%
“…The losses of copper to the slag are in three forms, copper oxide, copper sulphide and metallic copper, as dissolved oxides and as mechanically entrained matte or metal prills, respectively. [42] [44] It has been widely accepted that copper oxide in the slag in contact with metallic copper at high temperature is in the form of Cu20. [20] The reduction of cuprous oxides occurs simultaneously with the reduction of iron oxide.…”
Section: The Main Reactions In Slag Cleaning Furnacesmentioning
confidence: 99%